Development and implementation of a sewing robot with artificial intelligence using the design thinking method - Mynbayev M.T. , Мынбаев М.Т.; Baubekov S.D. , Баубеков С.Д.; Utesheva G.T. , Утешева Г.Т. (Рroblems of engineering and professional education, 2022)
This article presents the results of using the principles of the design of thinking that made it possible to create a sewing robot with artificial intelligence. The sewing robot is developed by modernizing existing sewing machines with deflected needles by using friction-transport-oriented devices for contouring parts of products.